Otonomi Khusus Papua dalam Hubungan dengan Gender, Generasi, dan Deforestasi: Sebuah Kajian Ekologi Politik Feminis - Manoby, Worry Mambusy; Siscawati, Mia; Dewi, Kurniawati Hastuti (Research and Development Agency Ministry of Home Affairs, 2023)
Forest governance within the framework of Special Autonomy in Papua is about improving the welfare of the Papuan people for indigenous communities. The conversion of customary forests into monoculture plantations is the main problem causing deforestation in Papua. In the patrilineal structure and patriarchal culture inherent in Papua, women only have forest management rights, while ownership rights are in the hands of men, and women will feel the impact more heavily than men when environmental degradation continues. Women's limitations in customary construction limit access and control over resources, experience vulnerability, are displaced from their living space and lose their source of livelihood. On the other hand, young people in Papua, as key actors in the process of economic and social change in Papua, have not been widely explored regarding their aspirations and role in forest governance. This study explores various academic literature and grey literature in the form of institutional work reports on forest governance in Papua with feminist political ecology focusing on the situation of gender, generations and young people, deforestation and forest governance in Papua. This study found that indigenous women and young people as part of indigenous communities are still often not considered and excluded from discussion spaces that determine the future of forest governance in Papua. Special Autonomy as respect, recognition and protection for the Papuan people. In the future, it is hoped that this can be a way to overcome injustice and inequality in the management of natural resources experienced by the people in Papua.